1998
DOI: 10.1038/bjc.1998.145
|View full text |Cite
|
Sign up to set email alerts
|

Captopril inhibits tumour growth in a xenograft model of human renal cell carcinoma

Abstract: Summary The effect of captopril on tumour growth was examined in a xenograft model of human renal cell carcinoma (RCC). Inoculation of the human RCC cell line SN12K-1 (106 cells) under the left kidney capsule of severe combined immunodeficient (SCID) mice resulted in the growth of large tumours, with an increase in weight of the inoculated kidney of 3.69 ± 1.63-fold (mean ± s.d.) when compared with the contralateral normal kidney. In mice treated with captopril (19 mg kg-1 day-' or 94 mg kg-1 day-1 administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 22 publications
2
76
1
Order By: Relevance
“…However, Ang II is known to stimulate neovascularisation (Fernandez et al, 1985), which in some cases is a requirement for tumour growth, while in vitro it stimulates cell replication in the absence of blood vessels (Paquet et al, 1990). ACE inhibitors retard growth of cancer cells in vitro (Reddy et al, 1995) and inhibit tumour growth in vivo (Hii et al, 1998), possibly through an effect on angiogenesis, while long-term use of ACE inhibitors may protect against the development of cancer (Lever et al, 1998). These results suggest that imidapril may inhibit growth of the MAC16 tumour by a mechanism unrelated to its effect on cachexia, and thus it is not possible to determine unequivocally whether imidapril has a direct anticachectic effect in this model.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ang II is known to stimulate neovascularisation (Fernandez et al, 1985), which in some cases is a requirement for tumour growth, while in vitro it stimulates cell replication in the absence of blood vessels (Paquet et al, 1990). ACE inhibitors retard growth of cancer cells in vitro (Reddy et al, 1995) and inhibit tumour growth in vivo (Hii et al, 1998), possibly through an effect on angiogenesis, while long-term use of ACE inhibitors may protect against the development of cancer (Lever et al, 1998). These results suggest that imidapril may inhibit growth of the MAC16 tumour by a mechanism unrelated to its effect on cachexia, and thus it is not possible to determine unequivocally whether imidapril has a direct anticachectic effect in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-bearing mice were administered captopril in their drinking water at 1, 10, 50, or 100 mg/kg/d; these are typical, murine therapeutic dosages. 23,24 Captopril attenuated tumor growth in a dose-dependent fashion ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…8 Investigation is needed beyond the observation period of most of these studies, 56 and additional experimental studies are needed also to study the mechanisms by which agents blocking the RAS may obtain their inhibitory effect on tumour growth and metastasis. 31 Angiotensin-converting enzyme inhibitors should be investigated in properly designed prospective clinical trials of patients with cancer. This approach faces the same problems as in trials with MMP inhibitors and other biological modifiers: identification of patients with minimal tumour burden, useful surrogate end points along with decisions about what doses to use.…”
Section: Discussionmentioning
confidence: 99%
“…In mice treated with captopril, there was a significant doserelated reduction in tumour development. 31 Pulmonary metastases of renal cell carcinoma showed prominent AT 1 receptor expression in both mice and humans, and candesartan treatment dramatically prevented lung metastatic nodules in mice, along with the inhibition of neovascularization and VGEF expression, compared with control mice. 32 Pancreatic adenocarcinoma Experimental studies using cultured hamster pancreatic cancer cells have shown that captopril and the ACEi CGS 13945 decreased cell proliferation, as well as the cell proliferation antigen (PCNA), a DNA polymerase cofactor that is used as a marker for synthesis phase.…”
Section: Renal Cell Carcinomamentioning
confidence: 95%